1983
DOI: 10.1128/iai.41.3.1217-1225.1983
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of poliovirus neutralization epitopes

Abstract: Poliovirus-neutralizing monoclonal antibodies were prepared against type 1, type 2, and type 3 wild laboratory (Mahoney, MEF1, and Saukett) and Sabin vaccine strains. Fifty-five poliovirus laboratory strains and field isolates were assayed by neutralization index test with a panel of homotypic monoclonal antibodies. A total of 27 monoclonal antibodies were used. Two categories of neutralization epitopes were found, i.e., cross-reacting (K), which is present on almost all strains of the same serotype, and strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…The data suggest that the attachment of 4-7 antibody molecules is required for the neutralization of picornaviruses of poliovirus/HRV dimensions. Studies by Horaud and colleagues (Blondel et al, 1986;Crainic et al, 1983;Diamond et al, 1985) have suggested that antibodies may bind to poliovirus without neutralization. This conclusion was made on the basis of studies using neutralizing antibodies which were analyzed for their activity (neutralization and binding) against a range of antigenic poliovirus variants (distinct serotypes and escape mutants).…”
mentioning
confidence: 99%
“…The data suggest that the attachment of 4-7 antibody molecules is required for the neutralization of picornaviruses of poliovirus/HRV dimensions. Studies by Horaud and colleagues (Blondel et al, 1986;Crainic et al, 1983;Diamond et al, 1985) have suggested that antibodies may bind to poliovirus without neutralization. This conclusion was made on the basis of studies using neutralizing antibodies which were analyzed for their activity (neutralization and binding) against a range of antigenic poliovirus variants (distinct serotypes and escape mutants).…”
mentioning
confidence: 99%
“…Thus, with respect to the prime phenomenon these two strains seemingly have an inverse relationship to each other. From the results of neutralization tests with crossabsorbed immune sera (Table 3), together with the general concept that enteroviruses have several neutralizing epitopes in the capsid proteins (3,8), we suggest that the Fukui strain has acquired a new antigenic determinant (s) but lacks one of the specific antigens present on the Bastianni strain. It is not clear whether the antigenic site(s) detected only in the Fukui 609/83 strain is a newly added structure independent of the original type-specific antigens or a derivative of the conformationally altered original epitopes.…”
Section: Discussionmentioning
confidence: 83%
“…The Fukui 212181 strain has acquired a new antigenic determinant(s) but lacks one of the specific antigens present on the Gregory strain. This finding suggests that several neutralizing epitopes might be present in the capsid proteins as in poliovirus [Crainic et al, 1983;Evans et al, 19831. It is not clear whether the antigenic site(s) detected only in the Fukui 212181 strain is a newly added structure independent of the original type specific antigens or a derivative of the conformationally altered original epitopes.…”
Section: Discussionmentioning
confidence: 98%